Electrocardiographic pattern changed in hospitalized leptospirosis and its association with disease severity - Bambang Irawan, Anggoro Budi Hartopo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2009)
Background: Electrocardiographic (ECG)changes have been observed in leptospirosis. The prevalence of ECG alterations may reach 80%. Despite of this finding,few studies have been conducted to assess ECGpatterns in only hospitalized leptospirosis patients in Indonesia. Objective: To reveal the prevalence and type of ECGalterations in hospitalizedleptospirosisand its association with disease severity. Methods: This was a cross-sectional study using medical record data. Patients hospitalized in Dr. Sardjito Hospital (January 2003 - December 2007) with leptospirosis (lCDXA27.9) were enrolled. Electrocardiogramstaken in 24 hours of admission were evaluated. Disease severity was determined based on clinical and laboratory findings. Association between disease severity with ECGrecordings were performed using Kruskal-Wallisand Chi square test. P value < 0.05 was significant. Results: Sixtysamples were analyzed.The prevalence of alterationof ECGrecordingswas 66.7%. Sinustachycardia was the most frequent (36.7 %). The most common arrhythmia was atrial fibrillation(10 %). Other abnormalities were alterationof ventricularrepolarization(8.3%1.extrasystoles (6.6%) and disorderof conduction (4.9%). Although not significant, those with atrial fibrillationtended to have the worst clinicaland laboratory findings. Conclusions: The prevalenceof alterationof ECGrecordingsin hospitalizedleptospirosiswas 66.7 %. Atrialfibrillation was the most frequent arrhythmia, and patients with this arrhythmia were likelyto have the most severe disease.